Temporal differences in the dependency on Phosphoinositide dependent kinase 1 distinguish the development of Vα14 iNKT cells, regulatory T cells and conventional T cells - Finlay, David (My University, 2010)
The present study uses two independent genetic strategies to explore the requirement for Phosphoinositide dependent kinase-1 (PDK1) in the development of mature T cell populations from CD4/CD8 double positive thymocytes. The data show that CD4/CD8 double positive thymocytes that do not express PDK1 or express a catalytically inactive PDK1 mutant fail to produce mature invariant V?14 NKT cells but can differentiate to conventional CD4, CD8 or regulatory T cell subsets in the thymus. The PDK1 requirement for V?14 NKT cell development reflects that these cells require the PDK1 substrate Protein Kinase B (PKB, also called Akt) to meet the metabolic demands for proliferative expansion in response to Interleukin 15 or antigen receptor stimulation. There is also constitutive PDK1 signaling in conventional ?/? T cells that is not required for lineage commitment of these cells but fine-tunes the expression of coreceptors and adhesion molecules. Also, while PDK1 is dispensable for thymic development of conventional ?/? T cells, peripheral cells are substantially reduced. This reflects a PDK1 requirement for lymphopenia-induced proliferation, a process necessary for initial population of the peripheral T cell niche in neonatal mice. PDK1 is thus indispensable for T cell developmental programs but the timing of the PDK1 requirement is unique to different T cell subpopulations.
PUBLISHED
Keywords: Immunology; T cells; Immunology, Inflammation & Infection